(3QSGdI aj eYQaI Gdbhis - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3CjhH Hf YKeGf s)
(3ChdgG (B:s
(3GdaUd GdChd ai Gdbhi GdfHGJjI hajg KdGKI eHGMK GdHMK GdChd ai JYOjOgG Gdbhi GdJi jTJQc ajg GdfHGJ hGdMjhGf s
(3BNQgG (B:s
(3acGf JUhQ GdeYbhdGJ CLRGA ZjQ eJfGgjI gPG Nda aGdfaS GdfGWbI eLQOI Yf GdeGOI hGdMeO dhGgH GdYbd s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs